2020
DOI: 10.26508/lsa.202000825
|View full text |Cite
|
Sign up to set email alerts
|

The RNA-binding profile of the splicing factor SRSF6 in immortalized human pancreatic β-cells

Abstract: In pancreatic β-cells, the expression of the splicing factor SRSF6 is regulated by GLIS3, a transcription factor encoded by a diabetes susceptibility gene. SRSF6 down-regulation promotes β-cell demise through splicing dysregulation of central genes for β-cells function and survival, but how RNAs are targeted by SRSF6 remains poorly understood. Here, we define the SRSF6 binding landscape in the human pancreatic β-cell line EndoC-βH1 by integrating individual-nucleotide resolution UV cross-linking and immunoprec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 120 publications
3
24
0
Order By: Relevance
“…The function of these different protein products can vary greatly and impact cellular function ( Alvelos et al 2018 ). Recent studies have suggested the importance of the unique splicing program innate to pro-endocrine cells, and how the functional outputs help steer the developmental process, yet it remains incompletely understood ( Juan-Mateu et al 2018 ; Singer et al 2019 ; Colli et al 2020 ; Alvelos et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The function of these different protein products can vary greatly and impact cellular function ( Alvelos et al 2018 ). Recent studies have suggested the importance of the unique splicing program innate to pro-endocrine cells, and how the functional outputs help steer the developmental process, yet it remains incompletely understood ( Juan-Mateu et al 2018 ; Singer et al 2019 ; Colli et al 2020 ; Alvelos et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of the candidate gene GLIS3 has a proapoptotic effect on human b-cells, which is mediated at least in part via downregulation of the splicing factor SRSF6 (also known as SRp55). SRSF6 inhibition impairs directly or indirectly the splicing of pre-mRNAs encoding key proteins for b-cell function (e.g., INSR, SNAP25), and survival (e.g., BIM-Small, BAX-b) (41,44).…”
Section: The As Connectionmentioning
confidence: 99%
“…First U2AF65 as part of the core spliceosome machinery was used to exemplify the di↵erent processing steps and its known binding properties were recaptured (Zarnack et al, 2013). Next, I characterized the so far unknown binding spectrum of SRSF6 in human pancreatic beta-cells (Alvelos et al, 2020). The identified binding motif matched a recent description in mouse cells (Müller-McNicoll et al, 2016).…”
Section: Discussionmentioning
confidence: 89%
“…Technically such approaches make use of antisense oligonucleotides (ASOs) to block specific binding sites. As a proof of principle, we already used ASOs in the related publication to modulate the splicing of the LMO7 gene (Alvelos et al, 2020). In the case of SRSF6 binding sites on further susceptibility genes could be used as potential targets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation